Curricula and methods for physician compassion training: protocol for a systematic review. Issue 9 (17th September 2018) - Patel, Sundip; Pelletier-Bui, Alexis; Smith, Stephanie; Roberts, Michael B; Kilgannon, Hope J; Trzeciak, Stephen; Roberts, Brian W
Abstract : Introduction: Compassionate patient care has been associated with improved clinical outcomes for patients. However, current evidence suggests that healthcare is experiencing a compassion crisis, with physicians frequently overlooking opportunities to treat patients with compassion. Although there is evidence that compassionate care can be enhanced through training interventions, it is currently unclear what specific skills and behaviours ought to be taught and how best to transfer this information to the learner. The objectives of this systematic review are to collate the world's literature on compassion training to determine (1) the specific skills and behaviours that should be taught (curriculum), and (2) the methods of training that are most effective at improving compassionate patient care. Methods and analysis: We will perform a qualitative systematic review of studies aimed at improving compassionate patient care among physicians and physicians in training. We will comprehensively search CENTRAL, MEDLINE, EMBASE and CINAHL. Additional recommended techniques for systematic reviews of complex evidence will be performed including pursuing selected 'references of references', electronic citation tracking and consulting experts in the field. Two investigators will independently review all search results. After identification and inclusion of papers, we will use a standardised form for data extraction. We will use tables to describe the study populations, interventions tested (including specific skill/behaviours taught and training methods used), outcome measures and effects of interventions on outcome measures compared with control groups. Where appropriate, meta-analysis will be used for quantitative analysis of the data. Ethics and dissemination: The proposed systematic review does not require ethical approval since no individual patient-level data will be collected. Results of this study will contribute to the understanding of compassion training and help inform the development of compassion training curricula. PROSPERO registration number: CRD42018095040.